STRATEGI PENGEMBANGAN KAMPUNG WISATA BERBASIS PESANTREN UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT DI KAMPUNG CILIANG KADUMERAK PANDEGLANG BANTEN - Icin Quraysin; Suhandi Suhandi; Listiawati Listiawati; Hadi Kurniawanto; Gatot Hartoko (LP2M Universitas Bina Bangsa, 2023)
Villages that have the potential to be made into pesantren-based tourism villages or Islamic religious education in Pandeglang Regency are Ciliang Village RT.04.RW.01, Kadumerak Village, Karangtanjung Pandeglang District, The purpose of this study is to analyze and examine the application of tourism village potential development strategies in Ciliang Village, and also analyze the role of several related parties so that the management of the potential of pesantren-based tourism villages is more optimal. The research method that researchers do is descriptive qualitative research. The research is a research whose data is qualitative. Data was obtained through, observation, interviews, and SWOT Matrix Analysis, to determine the strengths, weaknesses, opportunities and threats that Ciliang Village has in the development of rapid-based tourism villages. The results of this study show the need for tourism village development through the formation of tourism awareness groups, cooperation between the tourism village community and the Kadumerak village apparat and the Pandeglang Tourism Office and the right strategy in developing pesantren-based tourism villages in Ciliang Kadumerak Pandeglang village is through the concept of Bhinneka Tunggal Ika which reflects the diversity of cultures, traditions, natural beauty, crafts and the number of pesantren and educational institutions that become the identity or characteristic of Ciliang village then become a concentration of pesantren-based tourist village tourist destinations in Pandeglang Regency, Banten